Pain assessment using the NIH Toolbox - Cook, Karon F. (Lippincott Williams & Wilkins, 2013)
OBJECTIVE: Pain is an important component of health and function, and chronic pain can be a problem in its own right. The purpose of this report is to review the considerations surrounding pain measurement in the NIH Toolbox, as well as to describe the measurement tools that were adopted for inclusion in the NIH Toolbox assessment battery. METHODS: Instruments to measure pain in the NIH Toolbox were selected on the basis of scholarly input from a diverse group of experts, as well as review of existing instruments, which include verbal rating scales, numerical rating scales, and graphical scales. RESULTS: Brief self-report measures of pain intensity and pain interference were selected for inclusion in the core NIH Toolbox for use with adults. A 0 to 10 numerical rating scale was recommended for measuring pain intensity, and a 6-item Patient Reported Outcome Measurement Information System (PROMIS) short form for measuring pain interference. The 8-item PROMIS Pediatric Pain Interference measure was recommended as a supplemental measure. No specific measure was recommended for measuring pain intensity in children. CONCLUSIONS: Core and supplemental measures were recommended for the NIH Toolbox. Additional measures were reviewed for investigators who seek tools for measuring pain intensity in pediatric samples.